2010
DOI: 10.1097/aog.0b013e3181f74864
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Potential of Endometrial Polyps

Abstract: Based on data from observational studies, both symptomatic vaginal bleeding and postmenopausal status in women with endometrial polyps are associated with an increased risk of endometrial malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(64 citation statements)
references
References 49 publications
7
51
0
6
Order By: Relevance
“…Data from observational studies report that both symptomatic vaginal bleeding and postmenopausal status in women with endometrial polyps are associated with an increased risk of endometrial cancer. 11 Estrogen-producing tumors, unopposed estrogen therapy, cirrhosis, and tamoxifen also may result in excess estrogen stimulation to the endometrium. Although tamoxifen is an antiestrogen in breast tissue, it can have estrogenic activity in the endometrium.…”
Section: Risk Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Data from observational studies report that both symptomatic vaginal bleeding and postmenopausal status in women with endometrial polyps are associated with an increased risk of endometrial cancer. 11 Estrogen-producing tumors, unopposed estrogen therapy, cirrhosis, and tamoxifen also may result in excess estrogen stimulation to the endometrium. Although tamoxifen is an antiestrogen in breast tissue, it can have estrogenic activity in the endometrium.…”
Section: Risk Factorsmentioning
confidence: 98%
“…Based on data from observational studies, both symptomatic vaginal bleeding and postmenopausal status in women with endometrial polyps are associated with an increased risk of endometrial cancer. 11 Whereas sonohysterography also can detect these lesions, a tissue diagnosis may be warranted depending on the clinical context ( Figs. 1 and 2).…”
Section: Diagnosis Of Endometrial Cancermentioning
confidence: 99%
“…In our previous study, a higher occurrence of premalignant and malignant polyps was observed in postmenopausal females aged over 60 years with vaginal bleeding (5). Other studies have also shown an association between malignancy and certain risk factors, including obesity, arterial hypertension, diabetes mellitus and tamoxifen use (4,6). …”
Section: Introductionmentioning
confidence: 94%
“…The malignancy rate associated with endometrial polyps is low, and in a recent meta-analysis on the oncogenic potential of polyps, it was observed that the malignancy rate of endometrial polyps ranged between 0.8 and 8% in the different studies analyzed (4). In our previous study, a higher occurrence of premalignant and malignant polyps was observed in postmenopausal females aged over 60 years with vaginal bleeding (5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Lee et al [29] showed that important risk factors for malignancy in endometrial polyps are postmenopausal status and symptomatic vaginal bleeding. Their meta-analysis included 10,572 patients and found that 3.57% of polyps were malignant or showed complex atypical hyperplasia, but that the proportion increased to 5.42% in postmenopausal women and 4.15% in women with symptomatic vaginal bleeding.…”
Section: Discussionmentioning
confidence: 99%